The Role of Effective Strategy and Communication for Generation Z in Rural Communities - Ismayanti, Nurul; Rizky, M. Chaerul; Saragih, Khairunisa; Damanik, Fanna Oha (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
One important initial step in developing youth-oriented village development strategies is understanding Generation Z characteristics, including how they communicate, their interests, and aspirations. The purpose of this research is to find the most effective methods and communication approaches to support Generation Z in Karang Rejo Village. This research focuses on Karang Rejo Village in Stabat sub-district, which has 11,621 residents, consisting of 5,827 men and 5,794 women, making it the village with the second largest population in the Stabat. The selection of Karang Rejo as a research location was based on the fact that the village has a very representative demographic, with a balanced population composition between men and women. Using a combination of qualitative methods through in-depth interviews and direct observation, as well as quantitative approaches through surveys, this research aims to identify effective empowerment models. The results obtained are expected to serve as a strategic reference in designing development initiatives that are inclusive, innovative, and sustainable, so that the active involvement of all levels of society is encouraged.